Comparison of Mechanical Properties of Aged All-Ceramic Materials - Ali Riza Tuncdemir; Tugba Temizci (Selcuk Dental Journal)
Background: Our research aimed to compare the biaxial flexural strength of glass ceramic and two different monolithic zirconias after aging, examine the fracture surfaces with scanning electron microscopy (SEM) and perform elemental analysis with energy dispersive spectroscopy (EDS). Methods: Two types of monolithic CAD/CAM materials (Katana UTML and Prettau Anterior) and a lithium disilicate material (IPS emax Press) were selected for this study. All samples were aged with a thermal cycle of 10000 cycles. The biaxial flexural strength of the disc specimens was determined using the three-ball piston test and a universal testing machine. Biaxial flexural strengths were compared for each group (n = 10). All fractured samples were examined by SEM and elemental analyzes were performed with EDS. Data were analyzed by 1-way ANOVA and Tukey post hoc (p<0.05). Results: Prettau Anterior showed a statistically significant difference between the other groups (p<0.05). Following Prettau Anterior (1141.81 MPa), IPS Emax Press (278.86 MPa) and Katana UTML (216.14 MPa) showed biaxial flexural strength, respectively. Conclusion: Compared to the other materials evaluated, Prettau Anterior had much higher biaxial flexural strength. Katana UTML and IPS emax Press show similar strength over the long term. It is seen that the chemical structure of the materials has an effect on the mechanical capacity. KEYWORDS: Biaxial Flexural Strength, Lithium Disilicate Glass-Ceramic, Monolithic Zirconia